Equity Premium and Monetary Policy in a Model with Limited Asset Market Participation - Roman Horvath; Lorant Kaszab (Charles University in Prague, Institute of Economic Studies (IES), 2016)
This short paper shows that a New Keynesian model with limited asset market participation can generate a high risk-premium on unlevered equity relative to short-term risk-free bonds and high variability of equity returns driven by monetary policy shocks with zero persistence.
Keywords: E32; E44; G12; 330; limited participation; monetary policy; DSGE; equity premium